Pengaruh Program Literasi Al-Qur'an dan Dukungan Keluarga terhadap Kemampuan Membaca Al- Qur'an Siswa SMP IT Permata Cendekia Kabupaten Simalungun - Ramadan Syah Putra; Ali Imran Sinaga; Sahkholid Nasution (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research was conducted at Permata Cendekia Integrated Islamic Junior High School, Gunung Malela, Simalungun Regency. The purpose of this study was to explore the influence of the Quranic literacy program, family support, and their combined influence on students' Quranic reading abilities. The research method employed was quantitative with an ex post facto approach, where all eighth-grade students totaling 39 were selected as the research sample. The instruments used comprised questionnaires and tests, while data analysis was conducted using correlation and regression method. Several key findings emerged from this research. Firstly, there was an influence from the Quranic literacy program on Quranic reading abilities, indicated by a correlation coefficient of 0.459 and a determination coefficient of 0.211. The regression equation discovered was ŷ = 47.674 + 1.321X1. Secondly, there was observable influence from family support on Quranic reading abilities, with a coefficient of 0.618 and a determination coefficient of 0.382. The regression equation for this influence was ŷ = 21.222 + 0.637X2. Thirdly, it was found that there was a combined influence between Quranic literacy and family support on Quranic reading abilities, evidenced by a correlation coefficient of 0.635 and a determination coefficient of 0.403. The regression equation for this combined influence was ŷ = 21.093 + 0.491X1 + 0.540X2.